An N-terminal fragment of the gene 4 helicase/primase of bacteriophage T7 retains primase activity in the absence of helicase activity - Frick, David N. (The National Academy of Sciences, 1998)
Primase and helicase activities of bacteriophage T7 are present in a single polypeptide coded by gene 4. Because the amino terminal region of the gene 4 protein contributes to primase activity, we constructed a truncated gene 4 encoding the N-terminal 271-aa residues. The truncated protein, purified from cells overexpressing the protein, is a dimer in solution; the full-length protein is a hexamer. Although the fragment is devoid of dTTPase and helicase activities, it catalyzes template-directed synthesis of di-, tri-, and tetranucleotides. The rates for tetraribonucleotide synthesis and for dinucleotide extension on a 20-nucleotide template are similar for the full-length and truncated proteins. However, the activity of the primase fragment is unaffected by dTTP whereas the primase activity of the full-length protein is stimulated >14-fold. The primase fragment is defective in the interaction with T7 DNA polymerase in that primer synthesis cannot be coupled to DNA synthesis.